2013
DOI: 10.1002/arch.21108
|View full text |Cite
|
Sign up to set email alerts
|

DIFERENTIAL DNA SYNTHESIS IN Anopheles albimanus TISSUES INDUCED BY IMMUNE CHALLENGE WITH DIFFERENT MICROORGANISMS

Abstract: The induction of DNA synthesis in various tissues of Anopheles albimanus, in response to challenge with Saccharomyces cerevisiae, Micrococcus luteus, and Serratia marcescens, was analyzed by 5-bromo-2-deoxy-uridine (BrdU) incorporation. Microorganism-inoculated mosquitoes were fed with a sucrose solution containing BrdU and maintained alive for 5 days. Alternatively, abdominal carcasses of microorganisms-inoculated mosquitoes were cultivated in Roswell Park Memorial Institute (RPMI) medium supplemented with Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…gambiae (King and Hillyer, 2013), invertebrates lack the immune cell clonal expansion existing in vertebrates. We previously reported that de novo DNA synthesis occurs in mosquitoes (Hernandez-Martinez et al, 2013;Hernandez-Martinez et al, 2006), evidenced by the incorporation of BrdU and activation of PCNA in the tissues of these insects after an immune challenge. Such synthesis is most probably by endoreplication, as no mitotic cells have been observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…gambiae (King and Hillyer, 2013), invertebrates lack the immune cell clonal expansion existing in vertebrates. We previously reported that de novo DNA synthesis occurs in mosquitoes (Hernandez-Martinez et al, 2013;Hernandez-Martinez et al, 2006), evidenced by the incorporation of BrdU and activation of PCNA in the tissues of these insects after an immune challenge. Such synthesis is most probably by endoreplication, as no mitotic cells have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…To detect BrdU in midguts that were undergoing DNA synthesis, primed and unprimed samples were obtained as described in section 2.8.1 and processed as previously described (Hernandez-Martinez et al, 2013). DNA from midguts was obtained by phenolic extraction and incubated with 0.2 mg/ml of RNAse A (Gibco, Grand Island, NY, USA) for 1 h at 37 °C (Sambrook and Russell, 2001).…”
Section: Relative Quantification By Elisa Of Brdu In Mosquito Tissuesmentioning
confidence: 99%
“…This medium was used as a vehicle because mosquito mortality attributable to injection is reduced with this cell culture medium when compared to Schneider and Grace’s insect medium ( Log-rank x 2 = 131.006, P < 0.001), while no significant difference between PBS, Saline solution (0.9% NaCl) and MEM medium ( Log-rank x 2 = 1.075–9.18, P > 0.05) (Supplementary Figure S1 ) was observed. RPMI has been used in other studies (see Herrera-Ortíz et al, 2004 ; Hernández-Martínez et al, 2013a , b ; Moreno-García et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…In Anopheles albimanus , pathogen challenges with Plasmodium parasite, yeast wall and dead gram-negative bacteria activate the immune system, triggering DNA endoreplication mechanism (Hernandez-Martinez et al, 2006 ; Hernández-Martínez et al, 2013 ; Contreras-Garduño et al, 2015 ). Insofar, the molecules involved in this process have not been thoroughly unveiled.…”
Section: Introductionmentioning
confidence: 99%